Peran Kompensasi dan Disiplin Kerja dalam Upaya Meningkatkan Kinerja Pegawai Dinas Perindustrian dan Tenaga Kerja Kota Surabaya - Tjahjawati, Juni; Budiono, Budiono (Seminar Nasional Manajemen, 2025)
The background of the problem in this study is: how is the role of compensation on the performance of employees of the Department of Industry and Manpower of Surabaya City. Is there a role of work discipline on the performance of employees of the Department of Industry and Manpower of Surabaya City. The research method used in this study is a qualitative approach, with data collection techniques through interviews, observations, and documentation. With descriptive analysis data analysis techniques adhering to related literature. The results of the study indicate that adequate compensation and high work discipline play a significant influence on improving employee performance at the Surabaya City Industry and Manpower Office. Both act as the main driving factors to create a productive and high-performance work environment. Therefore, good management related to compensation and work discipline can be an effective solution in improving the quality of employee performance at the Surabaya City Industry and Manpower Office.